Defects and impurities in jarosite: A computer simulation study - Wright, Kathleen; Smith, A.; Hudson-Edwards, K.; Dubbin, W. (Elsevier, 2006)
Computer modelling techniques involving a rigid ion model have been used to investigate the defect structure and impurity site preferences in end-member K-jarosite. Calculated intrinsic vacancy energies show that the K2SO4 neutral cluster, with an energy per species of 1.34 eV, will be the most common defect in the pure phase. Defect reactions leading to vacancies on the Fe site have high energies, in excess of 4.0 eV per species, and are thus unlikely to occur in great numbers. However, the calculations show that divalent metal cations can be incorporated onto the Fe site via solution reactions with oxides leading to the formation of goethite. Calculated solution reactions are exothermic and thus predicted to be highly favourable. At K sites substitutions occur in the order Cd > Zn > Cu, but will be limited due to endothermic solution energies and structural considerations.